Developmental dyslexia in an orthography of intermediate depth: the case of european portuguese - Sucena, Ana (2021)
Fifteen Portuguese children with dyslexia, aged 9-11 years, were compared with reading and chronological age controls with respect to five indicators related to the phonological deficit hypothesis: the effects of lexicality, regularity, and length, implicit and explicit phonological awareness, and rapid naming. The comparison between groups indicates that Portuguese children with dyslexia have a phonological impairment which is revealed by a developmental deficit in implicit phonological awareness and irregular word reading (where younger reading level controls performed better than dyslexics) and by a developmental delay in decoding ability and explicit phonological awareness (where dyslexics matched reading level controls). These results are discussed in relation to the idea that European Portuguese is written in an orthography of intermediate depth.